Sequential binary decay of light nuclear systems: An assessment of statistical model codes - Nicolis, N. G. (HNPS Advances in Nuclear Physics, 2020)
The sequential decay of excited nuclei is described as a succession of binary processes involving fragments in their ground, excited-bound and unbound states. Primary together with secondary decays lead to the final mass and charge distributions. Asymmetric mass splittings involving nucleon emission up to symmetric binary ones are treated within the Weisskopf evaporation formalism, in a unified manner. This procedure was imple- mented in the Monte-Carlo multi-step statistical model code MECO (Multisequential Evaporation COde). We study the evolution of the calculated final mass and charge distributions from 40Ar* as a function of the excitation energy, up to complete dissociation. Our results are compared with the predictions of statistical evaporation codes based on different assumptions for the compound nucleus decay.